Multidisciplinary treatment of ischemic forms of diabetic foot - Y. V. Ivanova; O. M. Klimova; I. A Kryvoruchko; A. M. Korobov; V. O. Prasol; O. I. Pityk (Сучасні медичні технології, 2019)
Purpose of the study. The phototherapy, platelet growth factor and coating materials in the treatment complex using for improve the results of wound treatment in patients with the ischemic form of diabetic foot.